Effect of Work Motivation, Work Competency and Work Compensation on Employee Satisfaction at PT. Rezeki Mandiri Sentosa - Vanesa Vanesa; Juvelin Chandra; Hendy Chandra; Hendry Hendry (Institute of Computer Science (IOCS), 2021)
This study aims to determine the effect of work motivation, work competency, and work compensation on work satisfaction at PT. Rezeki Mandiri Sentosa. This type of research is explanatory research. The population in this study were all employees who worked at PT. Rezeki Mandiri Sentosa as many as 70 employees. The sampling technique that used is saturated sampling. In the study which will be distributed with questionnaires measured by a Likert scale. The data analysis used multiple linear regression analysis and the coefficient of determination as well as simultaneous test and partial test. The results showed that work motivation, work competency, and work compensation partially or simultaneously have a positive and significant effect on work satisfaction at PT. Rezeki Mandiri Sentosa. Based on the results of this study, the implications for management are to further improve work motivation, improve a work competency, improve the work compensation.